Adsorption Characteristics of Acid Orange 10 from Aqueous Solutions onto Montmorillonite Clay - Manpreet Kaur; Monika Datta (Adsorption Science & Technology)
Azo dyes have been identified as the most toxic of all dyes since they may be converted into potentially carcinogenic and/or mutagenic amines as a result of the reductive cleavage of the azo linkages after being released into the aquatic environment. Azo dyes are extensively used in industries such as textile, paint, plastic, cosmetic and paper. The aim of the present work was to develop a clay-based methodology which could successfully be employed for the removal of dyes from aqueous solution. The adsorption characteristics of C.I. Acid Orange 10 (AO 10) onto montmorillonite (MMT) and surfactant-modified MMT have been studied as a function of the dye concentration, the pH of the aqueous dye solution and the contact time. The dye adsorption efficiency of MMT was found to be much less than that of surfactant-modified MMT (CTAB-MMT and CPC-MMT), with 100% adsorption efficiency being observed for the removal of 160 ppm and 220 ppm of the dye by CTAB-MMT and CPC-MMT, respectively. In both cases, the adsorption data could be fitted by the Langmuir adsorption isotherm.